Grammatical Analysis of African American Vernacular English in The Eminem Show Album: A Linguistics Perspective - Ichwan Suyudi; Agung Prasetyo Wibowo; Luthfi Chanafiah Pasha (Institut Agama Islam Negeri (IAIN) Kendari, 2023)
Albeit the research on African American Vernacular English (AAVE) as nonstandard form of English spoken by African Americans in lower socioeconomic classes has been documented by many scholars, little is known about it from the perspective of Wolfram's theory. To fill this lacuna, the present study aims to elucidate the grammatical elements of Eminem's lyrics song in the album